Mile high with a vampire ebook - Sands, Lynsay (Argeneau, 2021)
In the latest Argeneau novel from New York Times bestselling author Lynsay Sands, an immortal and her mortal pilot are on the run from hungry vampires...and discover they're life mates along the way. Jet Lassiter likes being a pilot for Argeneau Inc. Perks included travelling to exotic locations and meeting interesting people, even if they are the blood-sucking kind. He's living the good life, until his plane goes down in the mountains and four of his passengers are gravely injured. They need blood to heal... and Jet is the only source. Quinn Peters never wanted to be immortal. Once a renowned heart surgeon, she was turned against her will and now she has to drink blood to survive. Before she can ask how her "life" can get any worse, she's in a plane crash. One of the few survivors, Quinn is desperate to get the mortal pilot to safety before her fellow immortals succumb to their blood lust and drain Jet dry. But hungry vampires are the least of their worries—the crash wasn't an accident, and someone is trying to kill Quinn. Will she and Jet find their happily ever after as life mates, or will her assassin find her first?